KEMAMPUAN MENYIMAK TEKS BERITA SISWA KELAS VIII SMP NEGERI 14 PEKANBARU - Estaurina, Nora; Razak, Abdul; Sinaga, Mangatur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study examines the ability to hear the eighth grade student text of the SMP 14 Pekanbaru. The purpose of this study was to describe the level of ability to listen to the news-text eighth-graders of SMP 14 Pekanbaru and knows there is a significant difference in message text listening comprehension class VIII SMP 14 Pekanbaru per gender and between groups of samples. This research data is the result of the skills test text message class VIII SMP 14 Pekanbaru, consisting of 8 classes listening with a population of 266 and the number of samples 160 The results tested in the use of normality test turned out to be a data class VIII SMP 14 Pekanbaru say not normal , By not normally the above data, then chi-square test goes to test a sample. Chi-square test of a sample is the problem how to solve high, the text message reads the eighth-grade text message students of SMP 14 Pekanbaru are low listening comprehension Class VIII SMP Negeri 14 Pekanbaru.Kemampuan hear. The next step researchers to measure Chi-square Two samples with, whether there is a significant difference between the group sex and eighth grade students of the SMP 14 Pekanbaru.Keywords: Listening, Text News.